Balthazar - Gray, Claudia (Sydney : HarperCollins Publishers, 2012)
When Balthazar agrees to help Skye Tierney, a human girl who once attended Evernight Academy, he has no idea how dangerous it will be. Skye's newfound psychic powers have caught the attention of Redgrave, the cruel, seductive master vampire responsible for murdering Balthazar and his family four centuries ago. Now Redgrave plans to use Skye's powers for his own evil purposes. Balthazar will do whatever it takes to stop Redgrave and exact his long-awaited revenge against his killer. As Skye and Balthazar stand together to fight him, they grow closer - first unwillingly, then undeniably. Balthazar realises his lonely world could finally be changed by her ...
For young adults.
Keywords: Vampires -- Juvenile fiction; Psychic ability -- Juvenile fiction; Love -- Juvenile fiction; Young adult fiction; Young adult fiction